Avaliação da Cinética de Secagem de Folhas de Pitangueira (Eugenia uniflora L.) em Secador de Micro-Ondas - Kawabata, Elise Yuriko (Universidade Federal de São Carlos, 2020)
Studies on the chemical composition of pitangueira (Eugenia uniflora L.) leaf, suggest that this species has great economic and medicinal importance. This is because it can be used to produce different extracts with antibacterial, antifungal and antioxidant activities. Since the moisture is responsible for an increase in the metabolic and chemical activities, as well as it promotes physical and chemical changes in the product, drying is commonly used to ensure the quality of the leaves after harvest. The objective of the present study is to dry Eugenia uniflora L. leaves in a microwave dryer and to compare the kinetics and drying rates under different input powers (120, 240 and 360W) for drying with and without vacuum. A vaccum pump was connected to a container inside the microwave chamber to produce a vacuum environment for drying. The tests were performed in duplicates and triplicates. Curves of moisture content as a fucntion of the drying time were analyzed and the drying rates were fitted to empirical equations (Page, Henderson and Pabis and Midilli and Kucuk). The increase in the input power and the use of vacuum contributed to decreasing the drying times. For vacuum-free drying, there was no significant reduction in the drying time as the input power was increased from 240 to 360 W. Predominantly, the drying curves presented only the decreasing drying rate period and Page's equation was the one that best fitted the experimental data.
Evaluation of the Drying Kinetics of Leaves of Pitangueira (Eugenia uniflora L.) in a Microwave Dryer
Keywords: folhas medicinais, desidratação, cinética de secagem.; ENGENHARIAS::ENGENHARIA QUIMICA::OPERACOES INDUSTRIAIS E EQUIPAMENTOS PARA ENGENHARIA QUIMICA; ENGENHARIAS::ENGENHARIA QUIMICA::PROCESSOS INDUSTRIAIS DE ENGENHARIA QUIMICA